Japanese Retail Industry After the Bubble Economy Development of the 100-yen Shops - Rahman, Md. Arifur (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book highlights the major institutional changes in the development of the Japanese retail industry after the bubble economy. The Japanese retail structure has been transformed from an abundance of small retail stores to chain stores by notable institutional changes with continuous variations in the post-1990s. It provides an insight into the impact of retail density on the household economy in the stagnant economy of Japan. The issues highlighted in this book include the background of the advent of 100-yen retail stores and strategic approach of the stores during the stagnant economy, a comparative analysis of Japanese 100-yen shops and dollar stores in United States, employment compliance of 100-yen shops and dollar stores in developing countries, factors that contributed to change the Japanese distribution channels after the 1990s, and determinants of retail density in Japan. The stagnant economy in the post-bubble period, along with changes in the large-scale retail store law, led consumers to shift from the most popular department stores to supermarkets and the cheapest retail alternatives. With its recent data and theories, this research work will be of interest to business and economics students and researchers in Japanese retailing and relevant areas.
Acknowledgement -- Abstract -- List of Figures -- List of Tables -- List of Abbreviations -- Chapter 1 Introduction -- Chapter 2 Key Features of Institutional Changes in Japanese Retailing Since the Bubble Period -- Chapter 3 Data and Methodology -- Chapter 4 Japanese 100-Yen Retail Chain in the Development of the Retail Industry after the 1990s -- Chapter 5 Dollar Stores: A Sense of Small Neighborhood in USA -- Chapter 6 Determinants of Retail Chain Diversity in Japan -- Chapter 7 Factors Affecting Changes in Distribution System in Japan -- Chapter 8 Summary and Conclusions -- References -- Appendices.
Keywords: International business enterprises; Retail trade; International Business; Trade and Retail